Ecosystem regime shifts disrupt trophic structure. Issue 1 (13th December 2017) - Hempson, Tessa N.; Graham, Nicholas A. J.; MacNeil, M. Aaron; Hoey, Andrew S.; Wilson, Shaun K.
Abstract: Regime shifts between alternative stable ecosystem states are becoming commonplace due to the combined effects of local stressors and global climate change. Alternative states are characterized as substantially different in form and function from pre‐disturbance states, disrupting the delivery of ecosystem services and functions. On coral reefs, regime shifts are typically characterized by a change in the benthic composition from coral to macroalgal dominance. Such fundamental shifts in the benthos are anticipated to impact associated fish communities that are reliant on the reef for food and shelter, yet there is limited understanding of how regime shifts propagate through the fish community over time, relative to initial or recovery conditions. This study addresses this knowledge gap using long‐term data of coral reef regime shifts and recovery on Seychelles reefs following the 1998 mass bleaching event. It shows how trophic structure of the reef fish community becomes increasingly dissimilar between alternative reef ecosystem states (regime‐shifted vs. recovering) with time since disturbance. Regime‐shifted reefs developed a concave trophic structure, with increased biomass in base trophic levels as herbivorous species benefitted from increased algal resources. Mid trophic level species, including specialists such as corallivores, declined with loss of coral habitat, while biomass was retained in upper trophic levels by large‐bodied, generalist invertivores. Recovering reefs also experienced an initial decline in mid trophic level biomass, but moved toward a bottom‐heavy pyramid shape, with a wide range of feeding groups (e.g., planktivores, corallivores, omnivores) represented at mid trophic levels. Given the importance of coral reef fishes in maintaining the ecological function of coral reef ecosystems and their associated fisheries, understanding the effects of regime shifts on these communities is essential to inform decisions that enhance ecological resilience and economic sustainability.